3
$\begingroup$

Evaluate: $$\mathop {\lim }\limits_{n \to \infty } \frac{{(n + 1){{\log }^2}(n + 1) - n{{\log }^2}n}}{{{{\log }^2}n}}$$

Intuitively, I feel that for large $n$, ${\log}(n+1) \approx \ {\log}(n) $. So, the above limit should reduce to:

$$=\mathop {\lim }\limits_{n \to \infty } \frac{{\{ (n + 1) - n\} {{\log }^2}n}}{{{{\log }^2}n}} \ = 1$$

However, can someone please suggest how can one mathematically show this.

Thanks!

$\endgroup$
4
$\begingroup$

If you want to be strict, write $$\log(1+n)=\log(n)+\log(1+\frac 1n)$$ So, the numerator is $$A=(n + 1) \log^2(n + 1) - n\log^2(n)=(n+1)\left(\log(n)+\log(1+\frac 1n)\right)^2-n \log^2(n)$$ Expanding the square and grouping $$A=a^2 n+a^2+2 a n \log (n)+2 a \log (n)+\log ^2(n)$$ where $a=\log(1+\frac 1n)\approx \frac 1n $ is small when $n$ is large.

Is this what you are looking for ?

Edit

Alternatively, you could set $n=\frac 1x$ and use Taylor series around $x=0$. Doing so, the entire expression will be $$\left(1-\frac{2}{\log (x)}\right)+x \left(\frac{1}{\log ^2(x)}-\frac{1}{\log (x)}\right)+\frac{x^2}{3 \log (x)}+O\left(x^3\right)$$

$\endgroup$
  • $\begingroup$ Nice one, but I have a doubt. when $n \rightarrow \infty$ then $a \rightarrow 0$. But from this how could you comment about $an$ or let say for $\frac{an}{\log (n)}$. $\endgroup$ – Rajat Nov 26 '15 at 9:46
  • $\begingroup$ $a\approx \frac 1n$ $\endgroup$ – Claude Leibovici Nov 26 '15 at 9:50
2
$\begingroup$

I would proceed as follows: $$\frac{(n+1)\log^2(n+1)-n\log^2n}{\log^2 n} = \frac{n}{\log^2n}(\log^2(n+1)-\log^2n) + 1 \left( \frac{\log(n+1)}{\log n}\right)^2$$ Now, the second summand tends to $1$ (for example, you can easily prove this using l'Hopital), while for the first summand you use $A^2-B^2=(A+B)(A-B)$ $$\frac{n}{\log^2n}(\log^2(n+1)-\log^2n) = \frac{n}{\log^2n}(\log(n+1)+\log n)(\log(n+1)-\log n)=$$ $$=\frac{n}{\log^2n}(\log(n^2+n))(\log(1+\frac1n)) \to 0$$ since $(\log(1+\frac1n))n \to 1$ and $\frac{\log(n^2+n)}{\log^2n} \sim \frac{2 \log n}{\log^2 n} = \frac{2}{\log n} \to 0$.

So finally your limit is $0+1 = 1$.

$\endgroup$
-1
$\begingroup$

It should be $$\lim_{n\to \infty} \left((n+1)(\frac{\ln(n+1)}{\ln n})^2 -n\right) = \lim_{n\to \infty} (n+1 - n) = 1.$$

$\endgroup$
  • 1
    $\begingroup$ This argument is incorrect. In fact, you get $1$ (which is the actual value of the limit) because you are lucky to have that exponent $2$. $\endgroup$ – Crostul Nov 26 '15 at 9:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.